GAMBARAN MINAT MAHASISWA SEMESTER VI ANGKATAN 2010 PROGRAM STUDI ILMU KEPERAWATAN (S-1) STIKES WIRA HUSADA YOGYAKARTA TERHADAP NURSING ENTERPRENERSHIP - Yohanes Agoes Passo Marey; Patria Asda; Beti Kristinawati (STIKES Wira Husada Yogyakarta, 2014)
ABSTRACTBackgrounds: A nursing entrepreneur is a nurse who combines abilities, nursing and business skills, andall resources he possesses to run his own business. A nursing entrepreneur provides clients’ treatment, health equipments, consultation, and education related to nursing.Goal: To description the interest of students of semester VI Nursing Study Program (S-1) Wira Husada Health Institute Yogyakarta in being nursing entrepreneurs. Methods: A quantitative research with product moment design, and purposive sampling to take research sample with 85 students for the sample out of the population of 109 semester VI students. The data were collected by distributing questionnaires and digging up the standard data. The data then were tested and analyzed. Results: The Students of Nursing Study Program (S-1) Wira Husada Health Institute Yogyakarta had a medium-leveled interest in being nursing entrepreneurs.